THE FIRST EVIDENCE OF INTERACTION BETWEEN THE ARMENIAN HIGHLAND AND EGYPT - Kazaran, Robert Petrosovic (History, Archeology and Ethnography of the Caucasus, 2025)
This article examines the possible interaction between Ancient Egypt and Išuwa, one of the states of the Armenian Highland. The interactions between the Armenian Highland and Egypt have a deep and intricate history, primarily documented since the Hellenistic period. However, a recently discovered inscription at the archaeological site known as the Kom el-Hettân, may provide new insights into the relationship between the Armenian Highland and Egypt. On the pedestal of one of the colossal statues of Amenhotep III, located within the temple complex, inscriptions identify various foreign nations through engravings of their representatives depicted as bound captives. The three captured figures represent the lands of “Ḫatti, Isyw, and Irṯw (Arzawa).” The land of Isyw may correlate with one of the ancient states of the Armenian Highland – Išuwa. This unique depiction prompts intriguing questions regarding the inclusion of an Išuwan figure in Egyptian iconography. The article is used general historical and comparative-historical analysis as the main research methods. The conducted research shows that there is no evidence that Egyptian expeditions ever reached the territory of the Armenian Highland or that they took captives from this region. This image may have a metaphorical, symbolic or propagandistic meaning, since the Egyptian pharaoh sought to emphasize the northern borders of his influence. An alternative explanation for the presence of the Išuwa country may lie in the context of repeated clashes between Mitanni and Ḫatti. It is possible that Hittite and Išuwan prisoners of war were sent by Mitanni to Egypt as diplomatic gifts and later depicted on the above-mentioned monument.
Keywords: Išuwa; Ḫatti; Arzawa; Egypt; Armenian Highland; interaction; Mitanni